Social Media Use in COPD Patients in Germany and Switzerland - Heimel, Markus; Jat, Hamida; Basch, Sarah; Gutzwiller, Florian S.; Biehl, Volker; Eckert, Jörg H. (Pneumologie, 2021)
Use of social media and the Internet has changed the information-seeking behaviour and exchange of experience and information by patients. Passive observation of such online interaction between patients (social media listening) is conducted in order to understand the burden of the disease, symptom perception, and expectations from a patient perspective. For most conditions, it remains to be established how representative the social media user community is for the overall patient population. In this study, we describe internet and social media use in a population of 570 COPD patients from Germany and Switzerland. This study population is a good representation of the overall patient population in Germany and Switzerland with regards to socioeconomic data. Patients were analyzed in an exploratory fashion whether usage of the Internet to obtain disease-specific information and exchanging on COPD via social media is associated with or is independent from certain socioeconomic criteria. About three-fourths of patients indicated using the Internet to search information about COPD and about a third of patients indicated using social media to exchange with others about their disease. Results indicated that among the patients using the Internet to seek information and among those sharing information via social media, patients with very severe COPD (GOLD stage 4) were overrepresented versus milder forms of the disease. Similarly, patients with more advanced educational background were also overrepresented in the groups using social media and Internet in relation to COPD. Differences in mean age were statistically significant, but surprisingly small between social media users and non-users. No relationship with regards to social media and Internet use for COPD were observed for domiciling situation and sex.